2007
DOI: 10.1007/s00421-007-0577-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between erector spinae muscle oxygenation via in vivo near infrared spectroscopy and static endurance time in healthy males

Abstract: The purpose of the study was to confirm the trends in right and left side muscle blood volume (Mbv) and muscle oxygenation (Mox) during the Biering-Sorensen muscular endurance (BSME) test, compare right and left side Mbv and Mox responses, and predict BSME time via Mox variables. Research suggests that during moderate intensity (approximately 20% of maximal volitional contraction) muscle contraction blood flow will decrease as a result of increased intramuscular pressure. Moreover, decreased muscle oxygenation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 32 publications
1
32
1
Order By: Relevance
“…Compared to a sustained isometric contraction, the electrical stimulation twitch protocols produced little or no decrease in oxygen levels compared to the resting values. Several previous studies have measured changes in oxygen levels to the Biering-Sorensen test [23][24][25]. These studies found sustained isometric exercise lowered oxygen levels, although the results seemed to vary between subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a sustained isometric contraction, the electrical stimulation twitch protocols produced little or no decrease in oxygen levels compared to the resting values. Several previous studies have measured changes in oxygen levels to the Biering-Sorensen test [23][24][25]. These studies found sustained isometric exercise lowered oxygen levels, although the results seemed to vary between subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in Oxy-hb and/or an increase in Deoxy-hb indicates opposite conditions, which may be seen in fatiguing phase. In this experiment, the spectroscope had one probe and two detectors with rubber shields which were fixed to the skin on the right side of the ESM at the level of L3, 3 cm from the vertebral column using a sticky gel sheet (Dieën et al 2009;Kell et al 2004;Kell and Bhambhani 2008). All EMG, NIRS, and load cell data was collected with a cable telemetric system at a 1,000 Hz sampling rate using the TEAC LX-10 series recorder (TEAC Corporation, Tokyo, Japan).…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…The re-224 searcher was positioned so that his line of vision was 225 aligned with the axis of the inclinometer needle. In or-226 der to ensure the test was a true measure of resistance 227 to fatigue the researcher gave constant verbal motiva-228 tion to maintain neutral spinal alignment, or "0" on the 229 inclinometer [15,54,65]. However at no point was ei-230 ther the researcher or participant aware of the amount 231 of time that had passed [54], as this has been shown to 232 be a factor directly influencing test results [8,12].…”
Section: Biering-sorensen Testmentioning
confidence: 99%